2002
DOI: 10.1523/jneurosci.22-03-01034.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Morphine Treatment Modulates the Extracellular Levels of Endogenous Enkephalins in Rat Brain Structures Involved in Opiate Dependence: A Microdialysis Study

Abstract: The endogenous opioid system is often assumed to play a role in vulnerability to drug abuse. However, controversial results have been reported regarding the levels of enkephalins or preproenkephalin in neurons of rodent brains after opiate administration. The present study was performed to determine the extracellular levels of enkephalins and its physiological antagonist cholecystokinin (CCK), using in vivo microdialysis in freely moving rats after morphine-induced physical dependence or positive place conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 61 publications
0
33
0
2
Order By: Relevance
“…Notably, in m-and d-, but not in k-, opiate-dependent rats, antagonistprecipitated or spontaneous opiate withdrawal induced a new and sustained inhibitory stimulus on FADD (lasting more than 2 days in the case of morphine withdrawal), which could be related to the large increase in the release of enkephalins (endogenous ligands for m-and d-opioid receptors) observed in the brains of chronic morphinewithdrawn rats (Mas Nieto et al, 2002), which also displayed higher numbers of c-Fos-positive neurons identified as enkephalinergic neurons (Veinante et al, 2003).…”
Section: Regulation Of Fadd By Opiate Drugsmentioning
confidence: 98%
“…Notably, in m-and d-, but not in k-, opiate-dependent rats, antagonistprecipitated or spontaneous opiate withdrawal induced a new and sustained inhibitory stimulus on FADD (lasting more than 2 days in the case of morphine withdrawal), which could be related to the large increase in the release of enkephalins (endogenous ligands for m-and d-opioid receptors) observed in the brains of chronic morphinewithdrawn rats (Mas Nieto et al, 2002), which also displayed higher numbers of c-Fos-positive neurons identified as enkephalinergic neurons (Veinante et al, 2003).…”
Section: Regulation Of Fadd By Opiate Drugsmentioning
confidence: 98%
“…In this frame, the present study investigated the hypothesis that increased titers of GluR1 and/or MDOR aAbs would mimic some specific modifications of reinforced behavior, classically reported in rats and mice following chronic morphine exposure (Nazzaro et al 1981;van Wolfswinkel et al 1985;Nieto et al 2002;He and Grasing 2004). For this reason, following immunization with the MDOR or GluR1 peptide fragments, we evaluated the behavioral phenotype in mice using a battery of validated tests, ranging from locomotion to drug reinforcement and physical dependence (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We extend our study to other opioid agonists and investigate the regulation of hDOR by enkephalins (Leuand Met-enkephalin), known as nonselective endogenous peptides (for review, see Reisine and Pasternak, 1996), and by SNC-80, a nonpeptidic ␦-selective agonist (Calderon et al, 1994). The choice of the two enkephalins was based on a previous study showing an increase of Met-enkephalin extracellular levels in brain of chronic morphine-treated rats (Mas Nieto et al, 2002). These data suggested that beside the sustained receptor activation by morphine, up-regulation of endogenous opioid system played a role in the development of tolerance by promoting opioid receptor desensitization.…”
mentioning
confidence: 99%